A conceptual framework for measuring airline business model convergence - Jost Daft; Sascha Albers (University of Cologne, Department of Business Policy and Logistics, 2012)
This paper develops a measurement framework that synthesizes the airline and strategy literature to identify relevant dimensions and elements of airline business models. The applicability of this framework for describing airline strategies and structures and, based on this conceptualization, for assessing the potential convergence of airline business models over time is then illustrated using a small sample of five German passenger airlines. For this sample, the perception of a rapprochement of business models can be supported. This paper extends the mostly qualitative and anecdotal literature on convergence in the airline industry and provides a platform for further empirical convergence studies.
Keywords: 650; airline strategy; convergence; business models; Luftverkehrsgesellschaft; Passagierluftfahrt; Geschäftsmodell; Strategisches Management; Theorie; Deutschland